The typographic imagination : reading and writing in Japan's age of modern print media - Shockey, Nathan (Studies of the Weatherhead East Asian Institute, Columbia University., 2020)
"A study of how Japan's modern commercial print revolution transformed ideas and practices of prose, language, philosophy, and politics. The book explores the habituation of new forms of reading and writing from the last years of the nineteenth century through the first decades of the twentieth, as the publishing industry made mass-produced books and magazines an inexorable part of everyday life. The book argues that this process precipitated a consciousness of the typographic text as a material medium and economic artifice with the power to critique and remake the modern world. Drawing from extensive archival research, with materials ranging from Meiji-era magazines to bookseller trade journals, strike bulletins, Esperanto primers, and declassified secret government censorship reports, The Typographic Imagination provides a layered, prismatic vision of Japanese literature, language, and culture in the age of modern mass media"--